Predictors of positive steps in the five-step stress echocardiography protocol in patients with postinfarction cardiosclerosis - T. M. Timofeeva; A. F. Safarova; G. S. Pavlikov; D. N. Vladelshchikova; Zh. D. Kobalava (Бюллетень сибирской медицины)
Aim. To study the frequency and predictors of positive steps in five-step stress echocardiography (SE) in patients with previous myocardial infarction (MI).Materials and methods. The single-center study included 75 patients (61.6 ± 9.8 years, 84% men) with previous MI. The median duration of MI was 1,231.0 (381.5; 2,698.5) days. All patients underwent exercise SE according to the five-step protocol. At step A wall motion abnormalities (WMA) were detected, at step B – the sum of B-lines, at step C – contractile reserve (CR) of the left ventricle (LV), at step D – coronary reserve (CorR) in the left anterior descending artery, and at step E – heart rate reserve.Results. The frequency of positive steps was 36.0% for step A, 18.7% for step B, 80.0% for step C, 53.3% for step D, and 50.7% for step E. Following the multivariate analysis, predictors of a positive step A (resting diastolic blood pressure (BP), p = 0.030, resting WMA index, p = 0.007), step B (taking β-blockers, p = 0.035; left ventricular (LV) mass index, p = 0.005), step C (increase in systolic BP (SBP), p = 0.011; increase in LV end-diastolic volume, p = 0.019; increase in LV ejection fraction, p = 0.008), and step D (taking angiotensin II receptor blockers, p = 0.026; increase in SBP, p = 0.012; increase in LV force, p = 0.038) were revealed.Conclusion. Identification of predictors of WMA during exercise, subclinical pulmonary congestion, and a decrease in CR and CorR in patients with previous MI may be a target for therapeutic intervention in order to delay the development of adverse cardiovascular events.